Analysis of High Strength Concrete Circular Columns under Axial and Lateral Loading Combinations (University of Thi-Qar Journal for Engineering Sciences, 2013)
Columns are vertical compression members which carry primarily axial Compression load. The axial load may be associated with bending moments in one or two directions.Analysis of high strength concrete columns with circular cross section and spiral transverse reinforcement was presented in this paper.A computer program was used to do the analysis of high strength circular concrete columns. The variables considered in this article were concrete strength ranging from 55 MPa to 80MPa, volumetric ratios of steel used to confine the core concrete, amount of main reinforcement and axial load level. The results indicate that as increase in the amount of lateral steel, main steel, axial load and increase in concrete strength resulted in increases in strength capacity of column. The deformability of high-strength concrete columns can be improved significantly through confinement. The results obtained in this research are agreed with results obtained by experimental and analytical study conducted by other authors.